Polonia Apartment (Green Architecture) - Rajaian Edwin F Sinambela; Nelson M Siahaan (Talenta Publisher, 2018)
Medan City, Indonesia's third largest city with a strategic position as the main gateway of Indonesia in the western region, must prepare itself to develop in facing variousopportunities and challenges as a metropolitan city. Polonia's ex-terminal complex post-relocation Polonia Airport is a region with the high potential to become a strategic trading center in Medan. Taking into consideration the availability of the existing area, the concept of vertical-shelter construction is chosen that can be used as a trading place, office or second residence is known as an apartment. The apartment can be defined as a building consisting of several residential units arranged in stages, and has the same space and facilities, to overcome the problem of density of occupancy rate and limited land in urban areas. Therefore, the concept of